Instrument tables equipped with local unidirectional airflow units reduce bacterial contamination during orthopedic implant surgery in an operating room with a displacement ventilation system. Issue 3 (September 2022) - Seth Caous, Josefin; Svensson Malchau, Karin; Petzold, Max; Fridell, Ylva; Malchau, Henrik; Ahlstrom, Linda; Grant, Peter; Erichsen Andersson, Annette
Summary: Background: Airborne bacteria present in the operating room may be a cause of surgical site infection, either contaminating the surgical wound directly, or indirectly via e.g. surgical instruments. The aim of this study was to evaluate if instrument and assistant tables equipped with local unidirectional airflow reduce bacterial contamination of the instrument area to ultra clean levels, during orthopedic implant surgery in an operating room with displacement ventilation. Methods: Local airflow units of instrument and assistant tables were either active or inactive. Colony forming units were sampled intraoperatively from the air above the instruments and from instrument dummies. A minimum of three air samples and two-three samples from instrument dummies were taken during each surgery. Samples were incubated on agar for total aerobic bacterial count. The mean air and instrument contamination during each surgery was calculated and used to analyze the difference in contamination depending on use of local airflow or not. All procedures were performed in the same OR. Results: 188 air and 124 instrument samples were collected during 48 orthopedic implant procedures. Analysis showed that local unidirectional airflow above the surgical instruments significantly reduced the bacterial count in the air above assistant table ( P <0.001) and instrument table ( P =0.002), as well as on the instrument dummies from the assistant table ( P =0.001). Conclusions: Instrumentation tables equipped with local unidirectional airflow protect the surgical instruments from bacterial contamination during orthopedic implant surgery and may therefore reduce the risk of indirect wound contamination.